2020
DOI: 10.1136/rapm-2019-100996
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of smoking in adults with spinal cord stimulators: a systematic review and meta-analysis

Abstract: BackgroundSmoking adversely impacts pain-related outcomes of spinal cord stimulation (SCS). However, the proportion of SCS patients at risk of worse outcomes is limited by an incomplete knowledge of smoking prevalence in this population. Thus, the primary aim of this systematic review is to determine the prevalence of smoking in adults with chronic pain treated with SCS.MethodsA comprehensive search of databases from 1 January 1980 to 3 January 2019 was conducted. Eligible study designs included (1) randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Most reviews focused on SCS therapy success and utility, and seven evaluated the predictors of SCS success 17 31 51 55 57 58 62. No reviews investigated the merits or disadvantages of trial screening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reviews focused on SCS therapy success and utility, and seven evaluated the predictors of SCS success 17 31 51 55 57 58 62. No reviews investigated the merits or disadvantages of trial screening.…”
Section: Resultsmentioning
confidence: 99%
“…Sparkes et al observed mania and hysteria to be associated with improved pain relief, while depression to be associated with poorer outcomes 51. Hooten et al observed that the prevalence of smoking in the SCS population overall was higher than in the general population 31. Overall, most reviews concluded that SCS therapy was better than CMM for chronic pain related to axial pain in the non-operated back, PSPS, PVD, DN, and chronic angina pectoris.…”
Section: Resultsmentioning
confidence: 99%
“…However, smoking is associated with accelerated spine degeneration, impaired surgical wound healing, and increased risk of infection in patients having spine surgery 74 75. A systematic review observed an overall smoking prevalence of 38% in patients with SCS,76 with differing rates among subgroups (56% when considered only for patients with PVD; and 28% in patients with lumbar spine diagnosis). Mekhail et al demonstrated that current smokers report significantly higher pain scores and opioid use (2.4 times) compared with non-smokers or former smokers 30 77.…”
Section: Committee Statements and Recommendationsmentioning
confidence: 99%
“…Comorbid psychiatric conditions such as major depressive disorder and anxiety disorders, which are particularly common within the chronic pain population, should be similarly optimized prior to surgery to maximize pain relief (37)(38)(39). Finally, tobacco use diminishes the responder rates of SCS, and providers should consider discussing smoking cessation with patients prior to impantation (40).…”
Section: Patient Selectionmentioning
confidence: 99%